2019
DOI: 10.28992/ijsam.v3i1.77
|View full text |Cite
|
Sign up to set email alerts
|

Financial Performance Mediation in the Influence of Islamic Corporate Governance Disclosure on the Islamic Social Reporting

Abstract: The results of the research on the social role of Islamic banks show inconsistency both domestically and abroad; this is the basis for conducting this research to re-explain the Islamic Corporate Governance (ICG) and Islamic Social Reporting (ISR) relationship, models. This study aims to examine the indirect effect of ICG disclosure on ISR disclosure with financial performance as a mediating variable in Islamic Banking in Indonesia. This study uses secondary data with annual report data sources and financial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 27 publications
3
8
0
Order By: Relevance
“…Overall, sharia governance (sharia supervisory board, independent commissioner and audit committee) influences sustainability reporting with financial performance (ROA) as a mediating variable. These results are consistent with the studies of (Jones, 2007), (Anas, 2014) and (Budi et al, 2019) that there is a significant influence between shariah governance on sustainability reporting with firm performance mediation variables. This indicates that sharia governance that is implemented well, will be able to encourage Islamic banking to be able to carry out operational activities efficiently and effectively.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, sharia governance (sharia supervisory board, independent commissioner and audit committee) influences sustainability reporting with financial performance (ROA) as a mediating variable. These results are consistent with the studies of (Jones, 2007), (Anas, 2014) and (Budi et al, 2019) that there is a significant influence between shariah governance on sustainability reporting with firm performance mediation variables. This indicates that sharia governance that is implemented well, will be able to encourage Islamic banking to be able to carry out operational activities efficiently and effectively.…”
Section: Resultssupporting
confidence: 92%
“…Our independent variable consists of 1) Sharia supervisory board (SSB) which is measured by the number of SSB in the Islamic bank; 2) Independent Board of Commissioners (In Com), measured by the number of Independent Com in the Islamic bank; 3) Directors' Meeting (BODM), measured by the number of We use return on assets (ROA) to measure financial performance (mediating variable). While previous studies (Suteja et al, 2017) and (Budi et al, 2019) use return on equity (ROE) as mediating variable in the relationship between in corporate governance and ISR, this study uses ROA as alternative of financial performance proxy. Since our initial analysis shows that the results with ROE didn't provide optimum result, we use ROA to provide new contribution in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the better the implementation of ICG, the better it will encourage Islamic banking to carry out and report on its social activities. The results of this study are in accordance with research conducted by Indrawaty & Wardayati (2016) and Budi et al, (2019)which found that the application of ICG has a positive and significant effect on ISR. However, the results of this study are not in line with the research of (Rahma & Bukair, 2015)which found that ICG had no effect on ISR.…”
Section: Effect Of Icg On Isrsupporting
confidence: 91%
“…The application of ICG will make companies more open in conveying useful information as a type of responsibility for stakeholders and the environment and furthermore society (Sahut andSwitzer, 2013;Stuebs andSun, 2015;Zubeltzu-Jaka et al, 2018). This is in accordance with research conducted by Indrawaty and Wardayati (2016) and Budi et al, (2019) which states that ICG has a positive and significant effect on ISR.…”
Section: Islamic Social Reporting (Isr) and Islamic Corporate Governa...supporting
confidence: 66%
“…Companies that have annual activities community empowerment through CSR programs are encouraged to collaborate with BWM. This synergy will accelerate the process of achieving the vision so that Indonesia's economic growth will quickly rise and play a role in economic resilience during the pandemic and post-pandemic recovery (Budi et al, 2019).…”
Section: Description Of Csr Performance and Micro Waqf Banks And Msme...mentioning
confidence: 99%